PEROVSKITE FROM SPURRITE-MERWINITE MARBLES OF THE KOCHUMDEK CONTACT AUREOLE: APPLICATION TO U-Pb DATING OF A THERMAL EVENT - A.S. Deviatiiarova; E.V. Sokol; S.N. Kokh; E.N. Nigmatulina (Минералогия)
The paper presents the results of the first LA-ICP-MS U-Pb geochronological studies of 60 perovskite grains from spurrite marbles of the Kochumdek contact aureole (East Siberia). Perovskite is a dominant accessory mineral of U- and Th-poor marbles, which formed at the contact with traps of the Kuz’movsky complex (southwestern margin of the Tunguska Syneclise). The chemically homogeneous perovskite is characterized by limited substitutions: Ti4+ → Zr4+ (up to 2.5 mol. % CaZrO3 ) and Ca2+Ti4+ → REE3+Fe3+ (up to 1.8 mol. % REEFeO3 ). Perovskite is the main host for Th (up to 1550 ppm), U (up to 450 ppm), Ti, Zr, and LREEs (La + Ce + Pr + Nd); the element incorporation ratios are KTh = 516–870 and КU = 374. The U-Pb isotopic age of perovskite of 248.0 ± 7.2 Ma is in agreement with isotopic age values of traps of the Kuz’movsky complex.